Biomarker Records Associated with Mass Extinction Events - Whiteside, J.; Grice, Kliti (ANNUAL REVIEWS, 2016)
The history of life on Earth is punctuated by a series of mass extinction episodes that vary widely in their magnitude, duration, and cause. Biomarkers are a powerful tool for the reconstruction of historical environmental conditions and can therefore provide insights into the cause and responses to ancient extinction events. In examining the five largest mass extinctions in the geological record, investigators have used biomarkers to elucidate key processes such as eutrophy, euxinia, ocean acidification, changes in hydrological balance, and changes in atmospheric CO2. By using these molecular fossils to understand how Earth and its ecosystems have responded to unusual environmental activity during these extinctions, models can be made to predict how Earth will respond to future changes in its climate.